PEMENUHAN KESEJAHTERAAN ANAK SAAT PANDEMI COVID-19: KASUS BANJIR KANAL TIMUR: Fulfillment of Child Well-being during the COVID-19 Pandemic: A Case Study of East Flood Canal - Benedicta Devina Sekar Ayu; Wahyuni Retno Wulandari (Faculty of Law, Universitas Trisakti, 2025)
The East Flood Canal is one of the slums located in Cipinang Besar Urban Village, East Jakarta. The aspects to be examined in this study are the issues of environment and the health of children living in the East Flood Canal, including ensuring that their basic needs are met for proper growth and development. However, in the East Flood Canal, children's rights have not been fully met during the COVID-19 pandemic, despite being regulated by the Child Welfare Law. Therefore, the main probelm is: What is the condition of children's growth and development related to health in the East Flood Canal during the COVID-19 pandemic? and have the efforts to fulfill children's welfare related to health been in accordance with what is stipulated in the Child Welfare Law? The research is of the Socio Legal type, using both secondary and primary. Research result and conclusion: condition of children during the COVID-19 pandemic in East Flood Canal is poor in terms of health due to physical, social, and economic environmental factors and the efforts by the Health Office and the surrounding community to ensure the welfare of children living in the slum settlement of the East Flood Canal have been inadequate.